Nilai Kearifan dalam Babad Banyumas - Kuntarto Kuntarto; Rindha Widyaningsih; Muhamad Riza Chamadi (Jurnal Lingua Idea, 2019)
Banyumas chronicle has an essential role as a medium of cultural preservation, philosophical meaning, and value from the ancestors to the next generation. This study aims to find religious, social values in the Banyumas chronicle. Banyumas chronicle used as primary data is the Wirjaatmadja Banyumas chronicle version. The data was strengthened by literature studies and interviews with cultural figures from Banyumas, who were concerned about local wisdom studies. Analysis of values by using the reflection of the character, meaning of occurrence, and occasion in the chronicle. Religious and social values obtained include the teachings of gratitude, religious values, the value of helping, the value of unity, the value of deliberation to reach consensus, the value of justice and general welfare, the value of peace and non-violence, and the value of family and harmony.